IMPROVING VOCABULARY MASTERY BY USING MULTISENSORY METHOD FOR DYSLEXIC STUDENTS IN THE FOURTH GRADE AT BIANGLALA HOME SCHOOLING BANYUWANGI - Rosi Oktaviani Putri; Tri Mulyati; Halim, Abdul (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
The goal of the research was how a multisensory method assisted dyslexic graders increase their vocabulary mastery. The low of vocabulary scores of preliminary study obtained by dyslexic students. It encouraged this research. This research was conducted at Bianglala homeschooling Banyuwangi. There were two cycles to this Classroom Action Research. Three meeting in cycle 1, and two meeting in cycle 2. Three dyslexic students were the subjects of this research. The data was collected through a vocabulary test in multiple choice form. The test consist of 10 items of abstract noun and concrete noun. The results showed that the students’ test scores in cycles I and II increased significantly. The students’ achievement in cycle I was 66.6% who achieved the minimum criterion, but in cycle II, it increased to 100% who passed the minimum criterion. In addition, the minimum score was reached. From cycle I to cycle II, students’ vocabulary increased. The students’ vocabulary mastery improved from cycle I to cycle II, according to the findings. It may be concluded that using the Multisensory Method can assist dyslexic students enhance their vocabulary mastery.